'Absolutely Free'? Freedom of Movement and 'the Police Power' in Federation Australia. Issue 1 (2nd January 2023) - Finnane, Mark
Abstract : In 2020, Australian businessman, Clive Palmer sued the Western Australian government over border restrictions imposed during the early stages of the Covid-19 pandemic. In February 2021 the High Court unanimously rejected Palmer's action, concluding that the Emergency Powers Act was a valid exercise of State power in the circumstances of a public health pandemic. Among the precedents used by Palmer was a decision a century ago in which the High Court quashed conviction of a discharged Victorian prisoner who had been arrested in New South Wales under that State's Influx of Criminals Prevention Act. In this article I contextualise that case (R v Smithers, 1912), the history of the legislation it addressed, and the concept of 'the police power' of the States that was raised as a limit to the freedoms embraced by section 92. I ask whether that concept deserves renewed attention in the wake of newly experienced emergencies.